1980
DOI: 10.1136/jcp.33.2.163
|View full text |Cite
|
Sign up to set email alerts
|

Serum alpha 2-macroglobulin levels in diabetes.

Abstract: SUMMARY Serum cx2-macroglobulin levels have been determined in diabetic patients by quantitative radial immunodiffusion and compared with those observed in age-and sex-matched controls. In addition, the results in diabetics have been analysed with respect to such variables as the age and sex of the patient, the duration of disease, treatment, control, and the occurrence of retinopathy or nephropathy.The (x2-macroglobulin levels in diabetic patients were found to be significantly higher than in ageand sex-match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
1

Year Published

1984
1984
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 9 publications
4
31
1
Order By: Relevance
“…We found no correlation between antithrombin III activity and a2-macroglobulin. Although it is generally accepted that a2-macroglobulin levels are higher in diabetics,3' 4243 the relation between retinopathy and a2-macroglobulin has remained uncertain because of other variables including age, duration of diabetes, metabolic control and nephropathy, which may influence a2-macroglobulin levels.4244 Previous studies, which often failed to consider these factors, have reported both higher a2-macroglobulin concentrations in diabetics with retinopathy3' 43 and comparable levels in retinopaths and non-retinopaths. 42 Our results are in keeping with those of Gray et al,45 who found no significant difference in a2-macroglobulin levels between diabetics with retinopathy and those without when all the above variables were taken into account.…”
Section: Resultsmentioning
confidence: 99%
“…We found no correlation between antithrombin III activity and a2-macroglobulin. Although it is generally accepted that a2-macroglobulin levels are higher in diabetics,3' 4243 the relation between retinopathy and a2-macroglobulin has remained uncertain because of other variables including age, duration of diabetes, metabolic control and nephropathy, which may influence a2-macroglobulin levels.4244 Previous studies, which often failed to consider these factors, have reported both higher a2-macroglobulin concentrations in diabetics with retinopathy3' 43 and comparable levels in retinopaths and non-retinopaths. 42 Our results are in keeping with those of Gray et al,45 who found no significant difference in a2-macroglobulin levels between diabetics with retinopathy and those without when all the above variables were taken into account.…”
Section: Resultsmentioning
confidence: 99%
“…C3 is an acute phase reactant of the complement system that represents a crucial effector of the acute phase response of innate immunity. Excessive complement activation and abnormal serum levels of C3 and A2M have been implicated in the pathophysiology of various inflammatory diseases [28-30], including AIH, systemic lupus erythematosus (SLE) [31], diabetes [32], and anorexia nervosa [30], etc. In order to primarily validate the sensitivity and specificity of C3 and A2M in AIH, serum levels of these two proteins were measured in other forms of hepatitis, including 10 patients with hepatitis B or hepatitis C. Therefore, serum levels of C3 and A2M can serve as markers of some disease activity, even a potential biomarker in relation to diagnosis for the disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma levels of a2-macroglobulin in diabetic patients are reported to be high (Almer et al 1974;Ambrus et al 1979;James et al 1980) and to increase in parallel with the rise of HbAlc (Watzke et al 1988). The increase of plasma a 2-macroglobulin may delay correction of thickening of glomerular basement membrane by inhibiting of neutral protease activity and therefore inducing diabetic nephropathy (Brownlee 1976).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that in diabetic patients, levels of a2-macroglobulin in blood increased irrespective of types of diabetes (Almer et al 1974;Ambrus et al 1979;James et al 1980). Furthermore, there is a positive correlation between plasm a2-macroglobulin levels and HbAlc (Watzke et al 1988).…”
mentioning
confidence: 95%
See 1 more Smart Citation